Distribuição de neurônios nitrérgicos no diencéfalo do mocó (Kerodon rupestris) - Reis, Maria Emanuela Martins dos (2016)
Nitric oxide (NO) is a simple molecule (N=O), a gas with a free radical property whose until the 80s was considered a member of a family of environmental pollutants and a potential carcinogen. Since its discovery in the nervous system, NO has been implicated in several functions, what suits with its wide distribution in the brain. NO has been described in the brain of many animal species, but it was not described in the brain of the rocky cave (Kerodon rupestris), an endemic rodent of the Brazilian caatinga that inhabits rocky areas and have crepuscular habits. Due to these interesting characteristics we aim to describe the NO distribution of the rocky cavy diencephalon. Using standard immunoperoxidase against nitric oxide synthase (NOS), the NO synthesis enzyme, and histochemistry for NADPH-diaphorase, we were able to indirectly identify the presence of nitrergic neurons throughout the entire diencephalon. The hypothalamus showed a high density of NOS-IR neurons in several nuclei, among them the supraoptic nucleus, supraoptic decussation and the lateral part of the retrochiasmatic area. With moderate density we have the lateral pre-optic area, the preocular magnocellular nucleus, the anterior parvocellular part and the medial parvocellular part of the paraventricular nucleus of the hypothalamus, the ventrolateral nucleus of the hypothalamus, the peduncular part of the lateral hypothalamic area and the posterior nucleus of the hypothalamus. The anterior division of the ventromedial nucleus of the hypothalamus and the dorsal hypothalamic area presented low density, and the lateral part of the medial pre-optic nucleus presented very low density. In the thalamus, NOS-IR neurons were present in the ventral geniculate nucleus with high density. In the lateral part of the lateral habenular nucleus, the ventral posterodorsal thalamic nucleus and the mediocaudal part of the posterior thalamic nucleus with moderate density. The paraventricular nucleus of the thalamus, zona incerta and the parafascicular thalamic nucleus, presented low density. Comparing our results with those described in other animals we can say that the nitric system is an evolutionarily well-conserved neurotransmitter system.